2010
DOI: 10.1002/btpr.528
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative production of an antimicrobial peptide royalisin and its antibody via an artificial oil‐body system

Abstract: Royalisin found in the royal jelly of Apis mellifera is an antimicrobial peptide (AMP). It has a molecular weight of 5.5 kDa, which contains six cysteine residues. In this study, royalisin was overexpressed in Escherichia coli AD494 (DE3) as two oleosin-fusion proteins for preparation of its antibodies and functional purification. The recombinant royalisin, fused with oleosin central hydrophobic domain in both N- and C-termini, was reconstituted with triacylglycerol and phospholipids to form artificial oil bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…The antibacterial defensins were also produced in E. coli using a divergent method. The royalisin defensin from the royal jelly of Apis mellifera has an important estimated production potential (0.192 mg/L of cell culture) when produced in an artificial oil-body system (AOB) over-expressed in E. coli [98]. Oil bodies are plant seed organelles for intracellular lipid storage, composed of a triacylglycerol (TGA) matrix surrounded by a phospholipid (PL) monolayer and specific proteins, such as the structural oleosin [99].…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial defensins were also produced in E. coli using a divergent method. The royalisin defensin from the royal jelly of Apis mellifera has an important estimated production potential (0.192 mg/L of cell culture) when produced in an artificial oil-body system (AOB) over-expressed in E. coli [98]. Oil bodies are plant seed organelles for intracellular lipid storage, composed of a triacylglycerol (TGA) matrix surrounded by a phospholipid (PL) monolayer and specific proteins, such as the structural oleosin [99].…”
Section: Discussionmentioning
confidence: 99%
“…Def-1 has been shown to be effective against Gram-positive bacteria (Fujiwara et al, 1990;Bachanová et al, 2002;Shen et al, 2012); however, some studies using recombinant Def-1 have also reported its activity against Gram-negative bacteria including Pseudomonas aeruginosa and Salmonella enterica (Tseng et al, 2011;Bílikova et al, 2015). In accordance with these previous studies, Pseudomonas aeruginosa seemed to be resistant to Def-1.…”
Section: Discussionmentioning
confidence: 99%
“…A bacterial expression/purification system to produce recombinant proteins was developed by using artificial oil bodies [141,[164][165][166][167][168][169]. In this system, a target protein was first overexpressed as an insoluble oleosin-fused polypeptide, collected from the pellet of cell lysate simply by centrifugation, assembled into artificial oil bodies, separated from oleosin, and then harvested by concentrating the ultimate supernatant.…”
Section: Protein Expression/purificationmentioning
confidence: 99%